Competence Development of Future Technological Education Teachers Based on an Integrative Approach - Rajabova Dilfuza Abdumajitovna (Zien Journals, 2023)
This article describes the forms of development of pedagogical and professional competence of technology teachers based on an integrative approach.
Keywords: technology; integration; integrative approach